2006
DOI: 10.1638/05-092.1
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Levels of Wild Steller's Eiders (Polysticta Stelleri) and Black Scoters (Melanitta Nigra) in Alaska Using a Portable Blood Lead Analyzer

Abstract: Sea duck populations are declining in Alaska. The reasons for the decline are not known; environmental lead exposure is one suspected cause. Thirty wild Steller's eider ducks (Polysticta stelleri) and 40 wild black scoter ducks (Melanitta nigra) were tested for blood lead levels using a portable blood lead analyzer (LeadCare; ESA, Inc., Chelmsford, Massachusetts 01824, USA). Sixty-seven and one-tenth percent of the sea ducks had undetectable blood lead levels, 30.0% had values indicating normal or background l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Using guidelines established for birds, lead exposure in foraging California leatherback turtles (0.20260.067 ppm) falls at the boundary between background level (,0.2 ppm), and recent exposure (0.2-0.590 ppm) to lead (Brown et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Using guidelines established for birds, lead exposure in foraging California leatherback turtles (0.20260.067 ppm) falls at the boundary between background level (,0.2 ppm), and recent exposure (0.2-0.590 ppm) to lead (Brown et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both cadmium and lead concentrations measured in the erythrocytes of Eurasian blackbirds Turdus merula can accurately estimate circulating levels, demonstrating that very small blood samples are sufficient to measure these metals ( Coeurdassier et al 2012 ). Portable blood analyzers have also been used to measure lead concentrations in blood within natural populations, which allows for immediate in-field assessment ( Brown et al 2006 ).…”
Section: Using Avian Biomonitors To Detect and Monitor Pollutantsmentioning
confidence: 99%
“…3,5,9 Results of studies found a good correlation between LCS and GFAAS on avian samples, with 93% agreement between methods on blood samples from waterfowl. 3 Furthermore, because analysis only takes minutes, captured birds need be held only briefly to determine the necessity of treatment before release. LCS could be useful in a large clinical veterinary practice for the same reasons it is useful in field research.…”
mentioning
confidence: 97%
“…LeadCare has been used for Pb detection in human medicine and to a limited extent in veterinary medicine. [3][4][5]7,12,13,16 The manufacturer recommends that the blood samples be analyzed within 24 hr of collection.…”
mentioning
confidence: 99%
See 1 more Smart Citation